Temporomandibular dysfunction and functional mandibular limitation - Guimarães, Élcio Alves; Makhoul, Kelly Duarte Lima; Boaventura, Cristina de Matos; Ferreira, Ana Luiza; Sousa, Lucas Resende; Silva, Renato Mota da; Lima, Kennedy Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The temporomandibular dysfunction (TMD) is one of the most complex disorders of the body, capable of triggering changes in mandibular function and speech articulation. In the case of teachers, probably due to long periods of speech, since it is known that most of them work in classrooms with too many students, end up making use of the voice incorrectly and may lead to changes in the function of the stomatognathic system. Objective: To investigate the association between TMD and mandibular functional limitation in teachers of an elementary school in the city of Uberlandia. Methods: The study was carried out in 49 teachers. The data were collected through Helkimo’s Clinical Dysfunction Index (IDCCM) and Mandibular Function Impairment Questionnaire (MFIQ). Results: It was observed that all teachers in both genders showed some degree of TMD and, consequently, the higher the TMD degree the greater is the changing the jaw function. Conclusions: Based on the data and through studies carried out with this group of teachers, it is concluded that as the TMD degree increases, it causes alteration of the mandibular function and can lead to a decreased in the mandibular amplitude and to limit movement.